The aesthetic and the pedagogical – two opposing notions? A comparative analysis of Polish and British blogs about children’s literature - Fornalczyk-Lipska, Anna (Scripta Neophilologica Posnaniensia, 2022)
Children’s literature belongs simultaneously to the literary and the educational sys-tem – this is why the notions of the aesthetic and the pedagogical seem to be crucial in its study. They are often seen as opposing each other. The dichotomy between them appears to be even more interesting when approached from a cross-cultural perspective. Whereas English authors of books for the young reader were among the first to support the development of the children’s book into an art form in its own right (around the middle of the 19th century), their Polish counterparts followed suit decades later, as earliest attempts at writing artistically and without excessive didacticism appeared in the 1930s. In this context, a question arises whether and to what extent these traditional approaches to children’s literature and critique are still topical. I will address this question on the basis of a qualitative analysis of themed blogs written about literature for the young reader published in Poland and in the United Kingdom in the recent years. Interestingly, blogs discussing children’s literature are not addressed directly to the child, but to the “mediator circle”, or “gate-keepers”, primarily parents, teachers and librarians. With the help of content analysis and discourse analysis tools, I will try to determine the main themes present in their discussion of children’s and young adult literature, and to address them from the perspective of the traditional dichotomy between the aesthetic and the pedagogical.